Suggestions for development of solar photovoltaic power generation projects in Guangdong Province. Issue 2 (May 2019) - Han, Miaomiao; Liu, Xinxi
Abstract: In this paper, the solar energy resources in Guangdong Province are divided into three categories according to the development and utilization value, and the development and evaluation of distributed photovoltaic projects and grid-connected photovoltaic projects are carried out for each region. According to the calculation results and sensitivity analysis, the development and evaluation suggestions for photovoltaic power generation projects in Guangdong Province are obtain.